Suppression of Cross-Band Coupling Interference in Tri-Band Shared-Aperture Base Station Antenna - Chang, Yu-Lin; Chu, Qing-Xin (IEEE transactions on antennas and propagation, 2022)
A tri-band shared aperture (TBSA) antenna is proposed to meet the new requirements of base station antennas for multi-band antennas fusion. The proposed TBSA (P-TBSA) antenna is composed of a lower-band (LB: 790-960 MHz) antenna, two columns of middle-band (MB: 1710-2170 MHz) sub-arrays, and a 4×8 array antenna operating at N78 band (HB: 3.4-3.6 GHz). The LB antenna is located in the center of a shared reflector. The MB sub-arrays are located around the LB antenna with a side-by-side scheme. The HB array antenna is located below the MB and LB antennas for MIMO (multi-input multi-output) application. The cross-band coupling interference existing in the P-TBSA antenna can be divided into scattering interference and common-mode interference, which will seriously deteriorate its performance. To suppress the scattering interference, an LB crossed dipole antenna with low RCS (radar cross section) at both MB and HB and a MB crossed dipole antenna with low RCS at HB are designed. In addition, the method of "path extension" is used to suppressed the common-mode interference. By taking the above measures, the distorted radiation pattern of the P-TBSA antenna are significantly recovered.